Relationship between dental arch WIDTHS and mandibular plane angle in untreated adults With Skeletal class II malocclusion - Batool, Iffat; Abbas, Assad; Yahya, Farhan; Ali Rizvi, Syed Ausaf; Ayub, Ali (Pakistan Armed Forces Medical Journal, 2011)
Objective: To investigate the arch width in untreated Class II subjects with average and high mandibular plane angles. Study Design: Cross sectional comparative study. Place and Duration of Study: The study was conducted in the orthodontics department of Armed forces institute of Dentistry Rawalpindi from Sep 2008 to March 2009. Patients and Methods: Pretreatment dental casts and cephalograms of skeletal class II patients with complete set of permanent dentition except third molars reporting to the OPD of Orthodontic department were selected. Records of 60 patients (30 high angle, 30 normal angle) were randomly selected out of the 240 records studied. Intermolar and intercanine widths were measured in millimeters using digital calipers. Mandibular plane angle was measured from cephalometric tracings using the SN Mandibular plane (GoGn SN) angle as used in Steiner’s analysis. Results: The mean intermolar width for the normal angle group was 49.18 ± 2.69 mm and 48.56 ± 4.44mm for the high angle group. The mean intercanine width for the normal angle group was 34.41 ± 2.33mm and for the high angle group it was 33.13 ± 2.60mm. Independent t test failed to show any significant ( p > 0.05 ) difference in the IMW between normal and high angle patients. However a significant ( p < 0.05 ) difference was observed in the intercanine width of the normal and high angle groups. Conclusion: In our study there was no significant difference of intermolar width whereas significant difference of intercanine width was found between normal and high angle cases.